DETERMINANTS OF COMPLIANCE WITH HEALTH AND SAFETY REGULATIONS IN NIGERIA’S CONSTRUCTION INDUSTRY - Nnedinma UMEOKAFOR; oniface UMEADI; David ISAAC (Journal of Construction Project Management and Innovation)
The accident rate of the construction industry is disproportionate to the number of its workers compared with other industries. Despite this, the Nigerian construction industry lags behind in tackling the health and safety (H&S) challenges posed by the hazardous activities of the industry and contextual issues Compliance with H&S regulations is one of the pi llars to achieving optimum H&S in the workplace; regrettably, its level is low in Nigeria. This low level of compliance with H&S regulations in Nigeria remains one of the major factors blamed for the challenging state of H&S in Nigeria, especially in the c onstruction industry. Hence, this paper examines the determinants of compliance with H&S regulations in Nigeria’s construction industry, unearthing the salient issues to compliance with H&S regulations in N igeria’s construction industry. Using compliance t heories, it explains the compliance behaviour of the Nigerian construction industry. Although studies on compliance with H&S regulations in developed countries abound, contextual influence prompts a study peculiar to Nigeria. A systematic review of availab le literature gathered through desk literature search and qualitative content analysis were conducted The result of this study shows that key determinants to compliance with H&S regulations in the Nigerian construction indu stry include: culture, client in fluence, inadequate legislation, activities of the informal construction sec tor, beliefs, enforcement of H&S regulations, bribery and corruption . It is evident from this study that contextual issues may explain compliance behaviour . This paper goes further to conclude that irrespective of the inadequate regulations and lack of governmental support, stakeholders in the construction in dustry and trade unions can improve H&S . It also recommends that: building planning departments in local councils be involved in H&S enforcement; in tender selection, preference should be given to construction contractors with good safety records; H&S professionals should exploit the economic benefits of good H&S management system to attract management commitment